Vidas caladas: a voz feminina em Graciliano Ramos - Santana, Lélia Maria Sampaio (2016)
Graciliano Ramos’s work has been studied under various aspects. However, studies on women in his work are limited to Sinha Victoria from Vidas Secas (Barren Lives), and/or Madalena from São Bernardo. This research developed an analysis of female characters in the fictional universe of the writer from Alagoas, namely: Luísa, from Caetés, Madalena, from São Bernardo, Marina, from Angústia (Anguish), and Sinha Vitória from Vidas Secas, adding Mrs. Maria Amelia, the author’s mother, a significant presence Infância, a book that merges memory and fiction. The interpretation of the texts was carried out from the perspective of social and historical context of the works, focusing on the female universe. In each work the characters are involved in different themes, Ramos created fictionally women ahead of their time; anticipating discussions that would be intensified years later. In order to support the analysis of the novels, the opening chapters address the critical author's fortune, contextualization, history, language and silencing, historical retrospective of women in Brazil and the pursuit of equality with men. We intend to demonstrate the importance of the female voice, although their speech is delivered at a time when women were just beginning the path of militancy for their rights, in the late nineteenth and early twentieth century.